Purchase order for supply & installation of MS Z-Louver railing works for the jogging track on roof for BRAC University new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and M R Corporation for the supply and installation of MS Z-Louver railing works Brac University new campus project.